Continuous flow knitting of a triptycene hypercrosslinked polymer. Issue 59 (5th July 2019) - Lau, Cher Hon; Lu, Tian-dan; Sun, Shi-Peng; Chen, Xianfeng; Carta, Mariolino; Dawson, Daniel M.
Abstract : Hypercrosslinked polymers suitable for carbon capture were produced in continuous flow synthesis using 10% of the time required for typical batch reactions, precluding the need for lengthy reactions to produce microporous polymeric adsorbents. Abstract : By replacing Lewis acids with Brønsted acids as catalysts, continuous flow synthesis of hypercrosslinked polymers is achieved within 10% of the time required for a typical batch reaction. Compared with batch-synthesised polymers, the flow-produced materials take up 24% more CO2, precluding the need for lengthy reaction protocols to yield high-performance hypercrosslinked polymers for carbon capture.